Treatment of Vitiligo Patients by Excimer Laser Improves Patients' Quality of Life. Issue 1 (January 2015) - Al-Shobaili, Hani A.
Background: Vitiligo can negatively affect patients' quality of life (QoL). Assessment of QoL provides relevant information about treatment benefits. Objectives: To examine the effects of excimer laser treatment on vitiligo patients' QoL and to identify overall patient satisfaction. The literature review failed to show any study concerning the same field. Methods: A total of 134 vitiligo patients (with 386 lesions) were studied. The Dermatology Life Quality Index (DLQI) was used to assess the effect of excimer laser treatment on patients' QoL. A visual analogue scale (VAS) was used to rate patients' overall life satisfaction and disturbance. Results: Excimer laser treatment significantly improved QoL in vitiligo patients, with improvement observed in five of six DLQI domains. Treatment-induced changes in the VAS score showed a significant decline in life disturbance and improvement in life satisfaction. Multivariate analysis revealed that sex and treatment duration were independent factors influencing treatment outcomes. Conclusions: Treatment of vitiligo with excimer laser can positively influence patients' QoL. Patients with multiple focal lesions should be treated by excimer laser even if some lesions may not show significant clinical improvement.